2016
DOI: 10.1016/j.bpsc.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cingulo-opercular Network Efficiency Mediates the Association Between Psychotic-like Experiences and Cognitive Ability in the General Population

Abstract: Background Psychosis is hypothesized to occur on a spectrum between psychotic disorders and healthy individuals. In the middle of the spectrum are individuals who endorse psychotic-like experiences (PLEs) that may not impact daily functioning or cause distress. Individuals with PLEs show alterations in both cognitive ability and functional connectivity of several brain networks, but the relationship between PLEs, cognition, and functional networks remains poorly understood. Methods We analyzed resting-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
25
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 71 publications
10
25
3
Order By: Relevance
“…Presence of sub-clinical psychosis has been associated with processing speed deficits as measured by the digit symbol task (Rossler et al 2015). In data from the Human Connectome Project, 21.6% of individuals endorsed at least one psychotic-like experience, and psychotic-like experiences were significantly negatively associated with general cognitive ability, replicating previous findings (Sheffield et al 2016). Further, individuals who endorse symptoms of schizotypy in the general population have below average cognitive performance (Dinn et al 2002) (Park et al 1995).…”
Section: Introductionsupporting
confidence: 82%
“…Presence of sub-clinical psychosis has been associated with processing speed deficits as measured by the digit symbol task (Rossler et al 2015). In data from the Human Connectome Project, 21.6% of individuals endorsed at least one psychotic-like experience, and psychotic-like experiences were significantly negatively associated with general cognitive ability, replicating previous findings (Sheffield et al 2016). Further, individuals who endorse symptoms of schizotypy in the general population have below average cognitive performance (Dinn et al 2002) (Park et al 1995).…”
Section: Introductionsupporting
confidence: 82%
“…20 Individual differences in network efficiency covaried with cognitive function, with the cortical and the subcortical networks making statistically independent contributions. These findings replicate observations made in 2 separate smaller samples 21,22 and were presaged by similar findings from independent researchers.…”
Section: Psychosessupporting
confidence: 79%
“…1,32 For example, Drysdale and colleagues 10 replicated the anxietyinsomnia-related depression biotype in patients with diagnoses of generalized anxiety disorder. The studies by Sheffield and colleagues [20][21][22] found the same psychosis-related connectivity patterns, irrespective of whether the patient's formal diagnosis was schizophrenia, schizoaffective disorder, or a bipolar mood disorder. Mary Phillips' research group reports that, in patients with bipolar depression, emotional dysregulation is associated with disturbed connectivity in the limbic circuitry implicated in negative mood states; 9 high sensation-seeking youth exhibit frontostriatal connectivity alterations across diagnoses.…”
Section: What Next?mentioning
confidence: 89%
“…Connectivity patterns differ across conditions, but show substantial overlap, especially hypoconnectivity within the default mode network and cingulo‐opercular network. This hypoconnectivity was found across psychotic disorders and in people with psychotic experiences 216‐218 . Similarly, poor efficiency in the connectivity of the cingulo‐opercular network was observed across psychotic disorders 219 and was associated with psychoticism in the general population 218 .…”
Section: Validity Evidencementioning
confidence: 88%